(untitled) (Vietnam Journal of Community Medicine, 2022)
Pelvic fracture is one of common causes of erectile dysfunction. Penile prothesis implantation is presented to these cases that poorly respond to other standard treatments. This reported a case of 33-year-old men with severe erectile dysfunction and urethral stricture following complex pelvic fracture due to a traffic accidents were successfully implanted three-piece inflatable penile prothesis at People’s hospital 115. At the third month of follow-up, this device has been worked effectively, patient could have ability to attain full erection for sexual intercourse. Both patient and partner are satisfied with their sexual lives.